2014
DOI: 10.1108/bfj-01-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Hungry for change: the food banking industry in Australia

Abstract: Purpose – Over the last 20 years, food banks in Australia have expanded nationwide and are a well-organised “industry” operating as a third tier of the emergency food relief system. The purpose of this paper is to overview the expansion and operation of food banks as an additional self-perpetuating “tier” in the response to hunger. Design/methodology/approach – This paper draws on secondary data sourced from the internet; as well as info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 13 publications
(19 reference statements)
1
81
0
2
Order By: Relevance
“…For example, in South Australia, the price to dump food waste is approximately $100 (AUD) per tonne. This cost is one hundred percent more than it was in 1990, and it is likely to increase as landfill sites become more remote and rare [60]. Thus, by donating their excess food, food donors gain significant savings in terms of storage, transport, and landfill charges.…”
Section: Costs and Benefitsmentioning
confidence: 95%
“…For example, in South Australia, the price to dump food waste is approximately $100 (AUD) per tonne. This cost is one hundred percent more than it was in 1990, and it is likely to increase as landfill sites become more remote and rare [60]. Thus, by donating their excess food, food donors gain significant savings in terms of storage, transport, and landfill charges.…”
Section: Costs and Benefitsmentioning
confidence: 95%
“…Similarly, they realized that initiatives of the associations were definitively not a solution for the over-production of food, but more a tool to prevent food poverty. This confirms that FRAs can contribute limitedly to food waste prevention and can hardly substitute for policy actions against the structural causes of hunger [89,90].…”
Section: Perception Of Social Impact Of Food Redistributionmentioning
confidence: 48%
“…Food rescue organisations and food banks can only redistribute what they receive from industry partners and other donors . It has been suggested that in Australia, food banks do more to help the food industry than to reduce food insecurity . As Booth and Whelan describe, ‘food manufacturers have surplus food they need to get rid of and charitable welfare agencies have clients who are in need of food assistance’ (p.1399).…”
Section: Discussionmentioning
confidence: 99%
“…Food banks and food rescue organisations gather, sort and redistribute food to community organisations who use this food to provide emergency food relief (EFR) to their clients . As in other high‐income countries, demand for EFR in Australia is increasing . The sector provides food to up to two million Australians each year, yet in 2013–2014, demand for EFR substantially outweighed supply…”
Section: Introductionmentioning
confidence: 99%